Utilizing Bentonite as a Natural Material to Enhance the Quality of Community Water Resources in the Urban Area - Ulhaq, Muhammad Zia; Hanan, Dafif; Salsabila, Athaya; Lala, Andi; Muslem, Muslem; Akbar, Zulhiddin; Zahriah, Zahriah (Heca Sentra Analitika, 2023)
In this study, the researchers investigated the state of water sources and the potential of bentonite as a water treatment agent. The study encompassed measurements of key water quality parameters for river and well water sources, including pH, TDS, conductivity, and salinity. The findings revealed that while pH levels were generally within the clean water standards, TDS values exceeded the threshold, particularly in river water samples. This suggests contamination due to urban activities and rising sea levels. Furthermore, the study explored using both activated and non-activated bentonite as an adsorption agent to remove contaminants from water sources. The results indicated that bentonite effectively increased pH levels, especially in well water samples, and significantly reduced TDS, conductivity, and salinity values, with non-activated bentonite being a preferred option for river water treatment and activated bentonite for well water treatment. These findings emphasize the potential of bentonite as a valuable water treatment solution. The specific characteristics of the water source should guide the choice between activated and non-activated bentonite. This tailored approach can lead to more effective and sustainable water treatment, contributing to improved water quality and availability for the community in the coastal region.